1988
DOI: 10.1136/thx.43.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular structure and function in chronic obstructive pulmonary disease.

Abstract: Cardiac catherisation data from eight patients with severe chronic obstructive lung disease and pulmonary hypertension at rest (> 25 mm Hg) were compared with those obtained from 14 patients with mild to moderate disease whose pulmonary artery pressure was within the normal range at rest (mean 15 (SEM 1) mm Hg), but increased with exercise (30 (2) mm Hg). We obtained lung sections from necropsy material from the group with severe disease, and from surgical specimens in the group with mild to moderate disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
2
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 14 publications
6
119
2
4
Order By: Relevance
“…15,17,27,29,32 However, other studies have not supported this relationship. 13,30 Some caution is needed in inferring a predilection for remodeling of smaller pulmonary arteries, because our measure of remodeling is partially dependent on the size of the vessel.…”
Section: Lobe and Pulmonary Arterial Sizementioning
confidence: 99%
See 2 more Smart Citations
“…15,17,27,29,32 However, other studies have not supported this relationship. 13,30 Some caution is needed in inferring a predilection for remodeling of smaller pulmonary arteries, because our measure of remodeling is partially dependent on the size of the vessel.…”
Section: Lobe and Pulmonary Arterial Sizementioning
confidence: 99%
“…15 Muscular pulmonary artery size was categorized, rather than treated as a continuous variable, 13,17,22,23 on an a priori basis as small (0.10-0.15 mm), medium (0.15-0.20 mm), and large (0.20-0.25 mm) in diameter.…”
Section: Vessel Sizementioning
confidence: 99%
See 1 more Smart Citation
“…(Sutter & Wang, 1993). TMP is available commercially in Diseases such as COPD can result in a persistent pulmonary China for use in the treatment of a variety of vascular diseases, hypertension which is associated with a high morbidity and notable ischaemic stroke (Beijing Research Institute of the mortality (Magee et al, 1988). Long term treatment of such Pharmaceutical Industry, 1977b;Chen & Chen, 1992) and patients is effectively limited to domiciliary oxygen as current pulmonary hypertension secondary to chronic obstructive vasodilator therapies cause systemic hypotension, and there is pulmonary disease (COPD) (Peng & Duan, 1991;Liu & Tang, a distinct clinical requirement for a therapeutic agent that is 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary hypertension associated with COPD has some histological similarities to idiopathic pulmonary arterial hypertension. Pathologic studies of lung specimens from patients with COPD have shown extensive vascular remodeling with prominent intimal thickening, medial hypertrophy, and muscularization of small arterioles (8,9). These findings have prompted clinicians to treat pulmonary hypertension in COPD with specific drugs for pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%